Psikologi Pendidikan Inklusif: Menciptakan Lingkungan Belajar yang Ramah Bagi Semua Siswa - Amahoru, Archristhea; Ahyani, Edi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This article proposes approaches and strategies for creating an inclusive educational environment that supports the success of all students, including those with special needs. The psychology of inclusive education is a key focus for understanding individual student differences and designing friendly and supportive learning approaches. By analyzing the various psychological aspects involved, this article explains how the application of inclusive principles can improve the participation, social development, and academic achievement of students with special needs. In addition, this article explores the important role teachers, administrators, and parents play in creating a supportive environment for all students, while creating an inclusive and empowered educational community. This research contributes to the practical and theoretical understanding of presenting inclusive education at different levels of education